Elevated α-Ketoglutaric Acid Concentrations and a Lipid-Balanced Signature Are the Key Factors in Long-Term HIV Control - Masip, Jenifer; Rallón, Norma; Yeregui, Elena; Olona, Montserrat; Resino, Salvador; Benito, José M.; Viladés, Consuelo; García-Pardo, Graciano; Alcamí, José; Ruiz-Mateos, Ezequiel; Gómez-Bertomeu, Frederic; Vargas, Montserrat; et al. (Frontiers in Immunology, 2022)
Long-term elite controllers (LTECs) are a fascinating small subset of HIV individuals with viral and immunological HIV control in the long-term that have been designated as models of an HIV functional cure. However, data on the LTEC phenotype are still scarce, and hence, the metabolomic and lipidomic signatures in the LTEC-extreme phenotype, LTECs with more than 10 years of viral and immunological HIV control, could be pivotal to finding the keys for functional HIV remission. Metabolomic and lipidomic analyses were performed using high-resolution mass spectrometry (UHPLC-(ESI) qTOF) in plasma samples of 13 patients defined as LTEC-extreme, a group of 20 LTECs that lost viral and/or immunological control during the follow-up study (LTEC-losing) and 9 EC patients with short-term viral and immunological control (less than five years; no-LTEC patients). Long-term viral and immunological HIV-1 control was found to be strongly associated with elevated tricarboxylic acid cycle (TCA) function. Interestingly, of the nine metabolites identified in the TCA cycle, α-ketoglutaric acid (P=0.004), a metabolite implicated in the activation of the mTOR complex, a modulator of HIV latency and regulator of several biological processes, was found to be a key metabolite in the persistent control. On the other hand, a lipidomic panel combining 45 lipid species showed an optimal percentage of separation and an ability to differentiate LTEC-extreme from LTEC-losing, revealing that an elevated lipidomic plasma profile could be a predictive factor for the reignition of viral replication in LTEC individuals.